Legal Protection for Land Rights Holders Who Are Victims of the Land Mafia - Rahmat Ramadhani (International Journal Reglement & Society (IJRS), 2021)
Cases over land disputes will be increasingly widespread. News of clashes during executions between the apparatus and the community in land cases every day color the reports in both print and electronic media. Land disputes cover a fairly large number. The continuing increase in land conflicts today, is a combination of the lack of efforts to resolve these conflicts systematically. Especially in the context of fulfilling the sense of justice and human rights of the victims on the one hand. There are several main causes that cause conflicts over land to increase, first, the existence of land mafias playing in land registration. This means that someone is trying to find the slightest opportunity by entering the official's signature. Second, the lack of knowledge of the apparatus, in this case someone who wants to register his land in order to get a certificate of his rights must really know how the process must be carried out or passed to register the land. The procedure used to collect data in this study is documentation, namely the guidelines used in the form of notes or quotes, searching legal literature, books and others related to the identification of problems in this study both offline and online. Analysis of legal materials is carried out using the content analysis method (centent analysis method) which is carried out by describing the material of legal events or legal products in detail to facilitate interpretation in the discussion. One of the government's efforts in eradicating the land mafia is to make regulations or technical instructions in this case the Ministry of Agrarian Affairs and Spatial Planning of the National Land Agency issued technical instructions Number 01/JUKNIS/D.VII/2018 concerning Prevention and Eradication of Land Mafia. In addition, the government's efforts through the National Land Agency to eradicate the land mafia are by filing good and correct land rights certificates. Archives have an important role for every agency or organization because the archive is evidence of the administrative track record for the agency or organization. Government Regulation No. 24 of 1997 concerning Land Registration which aims to provide legal certainty to the holders of rights to a parcel of land, housing units and other registered rights so that they can easily prove themselves as holders of the rights in question, to provide information to the parties concerned. interested parties including the Government so that they can easily obtain the data needed to carry out legal actions regarding registered land parcels and apartment units, for the orderly implementation of land administration. In order to protect the community as victims of the land mafia, in this case, of course, criminal sanctions are needed for land mafias who have violated the applicable laws and regulations. Criminal law enforcement is part of criminal politics (criminal policy) as one part of the overall crime prevention policy, indeed the implementation of criminal law is not the only hope to be able to resolve or overcome the crime completely.